2000
DOI: 10.4049/jimmunol.165.8.4632
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C ζ Plays a Central Role in Activation of the p42/44 Mitogen-Activated Protein Kinase by Endotoxin in Alveolar Macrophages

Abstract: Human alveolar macrophages respond to endotoxin (LPS) by activation of a number of mitogen-activated protein kinase pathways, including the p42/44 (extracellular signal-related kinase (ERK)) kinase pathway. In this study, we evaluated the role of the atypical protein kinase C (PKC) isoform, PKC ζ, in LPS-induced activation of the ERK kinase pathway. Kinase activity assays showed that LPS activates PKC ζ, mitogen-activated protein/ERK kinase (MEK, the upstream activator of ERK), and ERK. LPS did not activate Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
88
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 45 publications
4
88
4
Order By: Relevance
“…DISCUSSION We have shown previously that LPS induces production of PGE2 in human alveolar macrophages by increasing amounts of COX2 protein and mRNA (1,5,6). We have also shown that LPS increases the activity of PI3K and its downstream kinase, Akt (13,14). In this study, we show that PI3K activity regulates expression of COX2 and release of PGE2 negatively.…”
Section: Figsupporting
confidence: 51%
“…DISCUSSION We have shown previously that LPS induces production of PGE2 in human alveolar macrophages by increasing amounts of COX2 protein and mRNA (1,5,6). We have also shown that LPS increases the activity of PI3K and its downstream kinase, Akt (13,14). In this study, we show that PI3K activity regulates expression of COX2 and release of PGE2 negatively.…”
Section: Figsupporting
confidence: 51%
“…PKCb inhibitor is an anilino-monoindolylmaleimide compound that acts as a potent, cell-permeable inhibitor of PKCb isozymes (25). PKCz/l inhibitor is a myristoylated pseudosubstrate peptide inhibitor (Myr-SIYRRGARRWRKL-OH), which consists of pseudosubstrate peptide sequence derived from PKCz/l and is a cell-permeable, reversible, substrate competitive inhibitor (26). PKCd (V1-1; Myr-SFNSYELGSL-OH) and PKCε (Myr-EAVSLKPT-OH) inhibitors are cell permeable myristoylated translocation peptides inhibitors of PKCd and PKCε (27,28).…”
Section: Pkc Isoform Inhibitors and Inhibitor Treatmentmentioning
confidence: 99%
“…The pathways leading to MEK-ERK activation by LPS and CSF-1 may be distinct. The involvement of the upstream Ras-Raf components in MEK-ERK activation by LPS is controversial (15,(21)(22)(23)(24), whereas the alternative MAP-3-kinase, Cot/ Tpl-2 was required for LPS-induced MEK-ERK activation (25,26). The pathways leading to PI3K-Akt activation by LPS and CpG DNA still remain poorly defined.…”
mentioning
confidence: 99%